2008
DOI: 10.1099/vir.0.2008/001461-0
|View full text |Cite
|
Sign up to set email alerts
|

EBV LMP2A provides a surrogate pre-B cell receptor signal through constitutive activation of the ERK/MAPK pathway

Abstract: Latent membrane protein 2A (LMP2A) of Epstein–Barr virus (EBV) provides developmental and survival signals that mimic those of a B-cell receptor (BCR). Expression of LMP2A during B-cell development results in the ability of B cells to exit the bone marrow in the absence of a BCR and persist in the periphery, where they would normally undergo apoptosis. This study extends the current knowledge of LMP2A function by examining the growth properties of bone marrow B cells from TgE LMP2A mice. Despite the lack of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 45 publications
1
46
0
Order By: Relevance
“…LMP2A has been shown to activate the Ras/PI3K/Akt pathway (17,18,21), the MAP kinase pathway (22), NF-B (23), and Bcl-2 and Bcl-X L (18), each of which could contribute to the enhancement of cell survival observed in the LMP2A/ -MYC model. Bcl-2 and Bcl-X L induction are likely important mechanisms as they are anti-apoptotic proteins found further downstream in the apoptotic cascade induced by p53.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LMP2A has been shown to activate the Ras/PI3K/Akt pathway (17,18,21), the MAP kinase pathway (22), NF-B (23), and Bcl-2 and Bcl-X L (18), each of which could contribute to the enhancement of cell survival observed in the LMP2A/ -MYC model. Bcl-2 and Bcl-X L induction are likely important mechanisms as they are anti-apoptotic proteins found further downstream in the apoptotic cascade induced by p53.…”
Section: Resultsmentioning
confidence: 99%
“…Like LMP1, LMP2A has been shown to have a prosurvival function in B cells (17)(18)(19)(20). LMP2A can activate the Ras/PI3K/ Akt pathway (17,18,21), the MAP kinase pathway (22), NF-B (23), and Bcl-2 and Bcl-xL (18). We investigated whether LMP2A can protect B cells from apoptosis induced by MYC deregulation.…”
Section: S Ince Epstein-barr Virus (Ebv) Was First Identified It Hasmentioning
confidence: 99%
“…In that study, GST1-119, a glutathione S-transferase (GST) fusion protein containing 119 amino acids of the LMP2A cytoplasmic domain, coprecipitates with the ERK1 form of MAPK, suggesting that phosphorylation on the serine residues of LMP2A is induced by ERK1, followed by activation of MAPK signaling in B-cell lines [60]. A recent study on transgenic LMP2A mice showed that constitutive activation of the ERK/MAPK and PI3K/Akt pathways is involved in proliferation and survival [105]. A recent report claims that LMP2A activates the kinase activity of ERK/MAPK and JNK/MAPK in NPC cell lines, but not that of p38/MAPK [20].…”
Section: Mapk Pathwaymentioning
confidence: 99%
“…19 These data suggest that LMP2A imparts a surrogate pre-BCR signal in B cells that allows for survival in low concentrations of IL-7. Thus far, the data suggest that Notch1 signaling is important for LMP2A-mediated signaling.…”
Section: Resultsmentioning
confidence: 95%
“…19 Survival was measured at 48 hours by staining with annexin V according to product instructions and analyzing by flow cytometry.…”
Section: Survival Assaymentioning
confidence: 99%